Islam and Natural Resources Technology - Achmad Fachruddin Syah; Fahmi Amhar (Perhimpunan Intelektual Muslim Indonesia, 2022)
This paper aims to understand the Islamic view of advanced technology and also presents examples of technology and its application in natural resource management.This paper uses secondary data from reference books, proceedings, national and international journals.The emphasis of the analysis is qualitative descriptive.The results of the analysis showed that Islam is a religion that does not reject the existence of modernity.Even Islam strongly encourages its people to master science and technology.One of these advanced technologies is remote sensing technology.The integration of remote sensing technology and geographic information systems has many benefits and uses for human life, such as for detect potential fish distribution area, mapping habitat benthic in small island, forest landcover change,large scale topographic mapping,and others.Science and technology developed in the order of the Islamic system will provide mercy for the whole world.